A multi‐centre study to explore the feasibility and acceptability of collecting data for complex regional pain syndrome clinical studies using a core measurement set: Study protocol*. (11th July 2019) - Grieve, Sharon; Brunner, Florian; Buckle, Lisa; Gobeil, Francois; Hirata, Hitoshi; Iwasaki, Norimasa; Moseley, Lorimer; Sousa, Gudson; Vatine, Jean‐Jacques; Vaughan‐Spickers, Nicole; Xu, Jijun; McCabe, Candida
Abstract: Objectives: This international, multicentre study will inform the final data collection tools and processes which will comprise the first international, clinical research registry for complex regional pain syndrome (CRPS). This study will: (a) test the feasibility and acceptability of collecting outcome measurement data using a patient reported, questionnaire core measurement set (COMPACT [C oreO utcomeM easurement set for complex regionalPA in syndromeC linical sT udies]); and (b) test and refine an electronic data management system to collect and manage the data. Methods: A maximum of 240 adults, meeting the Budapest diagnostic clinical criteria for CRPS type I or II, will be recruited across eight countries. The COMPACT questionnaire will be completed on two occasions: at baseline (T1) and 6 months later (T2). At T2, participants will choose to complete COMPACT using a paper or electronic version. Participants will be asked to feed back on their experience of completing COMPACT via a questionnaire. A separate questionnaire will ask clinicians to feed back their experience of data collection. Analysis: The study is not aiming to derive statistically significant data but to ascertain the practicalities of collecting data, using the COMPACT questionnaire set, across a range of different cultures and populations. At the end of the study, a single workshop will be convened to review the findings and agree the final documents and processes for the international registry.